2013
DOI: 10.1093/sf/sot075
|View full text |Cite
|
Sign up to set email alerts
|

It's Who You Work With: Effects of Workplace Shares of Nonstandard Employees and Women in Japan

Abstract: Previous research on workplace composition has not addressed how the share of nonstandard employees affects individual workers' opportunities and well-being. Moreover, existing studies generally assume that the effect of a group's numerical representation is mediated through the group's relative power and status within establishments. This study asks whether workplace composition matters when the size of each social group has little impact on its relative status. Specifically, I examine the economic and psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Japanese women place more importance on a future marital partner's earning capacity than men do (NIPSSR, 2017). Because workers in workplaces with a higher share of fixed-term employees are paid less and have fewer opportunities for promotions (Yu, 2013), they are less likely to meet a potential partner with their desired earning capacity in their workplace. The lack of places to meet partners may explain why unemployed/inactive or fixed-term employees are less likely to have a partner than those with a permanent employment.…”
Section: Discussionmentioning
confidence: 99%
“…Japanese women place more importance on a future marital partner's earning capacity than men do (NIPSSR, 2017). Because workers in workplaces with a higher share of fixed-term employees are paid less and have fewer opportunities for promotions (Yu, 2013), they are less likely to meet a potential partner with their desired earning capacity in their workplace. The lack of places to meet partners may explain why unemployed/inactive or fixed-term employees are less likely to have a partner than those with a permanent employment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the same study, it was also found that overall 21% respondents think that it is bad for the economy considering India where 51% respondents see trade unions as bad for country's economy. Additionally, work-related distress (Yu 2013), wage, working hours (Medagyesi Zlyomi 2016) and working schedule and leave provisions (Makabe et al 2015), all affect worker's job satisfaction and quality of life.…”
Section: How Important Are Precarity and Decent Work Conditions To LImentioning
confidence: 99%
“…In addition, among male employees, 18.9% are nonstandard employees, whereas this percentage is 53.8% among female employees (MHLW, ). In Japan, nonstandard employees are treated as outsiders in their workplaces and are deprived of protection, opportunities, rewards, and benefits, whereas training opportunities and job security are provided to standard employees under the lifetime employment system (Yu, ). Past studies have mainly used three explanations—cultural, social, and economic—to explain the pervasive gender inequality in the labor force and family life.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the highly unequal gender division of labor among spouses in Japanese society calls for investigating the different mechanism of inequity between single‐father and single‐mother families. In Japan, a high proportion of women quit their jobs after marriage, particularly after childbirth (Shirahase, ), and they are more likely to be hired as nonstandard employees even if they return to the labor force (Yu, ). In addition, the cultural belief of intensive mothering, with mothers bearing the chief responsibility and investing their time and skills in child rearing and child's education, is pervasive (Bumpass, Rindfuss, Choe, & Tsuya, ; Honda, ).…”
mentioning
confidence: 99%